Spatial interpolation of in situ data by self-organizing map algorithms (neural networks) for the assessment of carbon stocks in European forests - Stümer, Wolfgang; Kenter, Bernhard; Köhl, Michael (Forest ecology and management, 2010)
Self-organizing maps (SOMs) are an advanced neural networks application. SOMs were applied for the spatially explicit estimation of forest carbon stocks for a test region in Thuringia (Germany). The approach utilizes in situ national forest inventory data and satellite remote sensing data (Landsat 7 ETM+) and provides maps showing a high-resolution spatial distribution of forest carbon stocks. The generated maps are compared to alternative estimates obtained by the k-nearest neighbour (kNN) method—a remote sensing based carbon assessment. Beside maps the SOM- and kNN-approaches were utilized to calculate statistical estimates of carbon stock and growing stock. The statistical estimates were validated by calculating bias and mean square errors with reference to in situ assessments. SOM- and kNN-approaches have been tested in a forested region in Central Germany. The results show that SOMs are an approach that has the ability to reproduce the spatial pattern of forest carbon stocks. SOMs are—with some restrictions—comparable to spatially explicit estimates generated by the kNN-method.